The Evaluation of Circulating Tumor DNA and Carcinoembryonic Antigen Levels and Relationship with Clinicopathological Risk Factors and Prognostic Indices in Colorectal Cancer Patients: ctDNA and CEA Relationship in Colorectal Cancer - YASLIKAYA, Şendağ; TÜRKER, Mehmet; AYDINALP CAMADAN, Yasemin; KIDI, Mehmet Mutlu; BİTER, Sedat; ASARKAYA, Esra; ASOĞLU RÜZGAR, Hatice; ATAŞ İPEK, Şüheda; KARA, İ.Oğuz; ŞAHİN, Berksoy (Scientific Reports in Medicine, 2024)
Objective: Colorectal cancer (CRC) is a leading cause of cancer-related mortality worldwide. ctDNA has emerged as a promising biomarker for CRC management, offering real-time insights into tumor burden and genetic mutations. This study investigates the correlation between CEA levels, ctDNA, clinicopathological factors, and treatment outcomes in early and advanced CRC patients.Methods: The study retrospectively analyzed data from CRC patients, including  early-stage disease and metastatic disease. ctDNA levels, demographic data, and clinical parameters such as CEA, inflammatory indexes, and tumor characteristics were evaluated to determine correlations with treatment outcomes.Results: The study included 20 patients, with 60% diagnosed at the metastatic stage.  The study found no statistically significant correlation between ctDNA levels and disease stage, recurrence, or overall survival. While CEA and ctDNA levels were measured, they did not demonstrate a significant relationship with treatment outcomes. Notably, ctDNA levels were higher in metastatic patients, though this was not statistically significant.Conclusion: Despite its potential, the integration of ctDNA as a routine biomarker in CRC care faces challenges, including variability in measurement techniques and cost-effectiveness. However, ctDNA's ability to guide personalized treatment strategies and monitor disease recurrence holds promise. The study's findings align with previous research, suggesting ctDNA as a poor prognostic indicator, though further research is needed. ctDNA represents a significant advance in CRC management, offering non-invasive, real-time insights into tumor dynamics. Ongoing research is expected to solidify its role in personalized treatment planning, potentially leading to more effective and tailored therapies for CRC patients.